36 The effectiveness of sterile technique in reducing false-positive blood culture results in qatif central hospital emergency department. (25th October 2019) - AL-Bazroun, Mohammed; ALKhunaizi, Auday; Al-Hamad, Arif; Ismail, Ali; Talib, Zahra; Twoailb, jaffar AL-; Ibrahim, Maha al; Alquraini, M
Abstract : Background: Blood culture contamination is a common and preventable problem in the emergency department (ED). In previous studies, changing the process of ED blood culture collection into a more sterilized procedure r esulted in a substantial reduction in the rate of blood contamination. The present study assessed the degree of blood contamination and evaluated the effect of using a sterile technique with monitoring and feedback on contamination rate over a 1-year period. Methods: We documented the rate of blood contamination among blood samples sent from the ED in the period from January 2016 until March 2016. A workshop for all ED nurses was held in March 2016 by clinical nurse instructors and this was followed by daily bedside teaching sessions for the whole study period. Nurses were instructed and audited on proper sterile blood withdrawal techniques. During the intervention period, we measured the rate of blood contamination for the period from April 2016 until September 2016. Results: Our average contamination rate dropped from the baseline of 12.6% (58 out of a total of 736 samples) to an average contamination rate of approximately 5.6% (122 out of a total of 1549 samples), with an odds ratio of 0.411 (95% CI 0.303- 0.559; p<0.001). Conclusion: Changing the method of blood culture collection from the commonly used aseptic technique to a sterile process resulted in significant reductions in blood culture contamination in a busy community hospital ER. Monitoring the implementation process was important to identify and overcome operational challenges. In addition, this study could be a good initiative to start a multicentric quality improvement project to reduce blood contamination in the neighboring community and public hospitals.